Thirty-day Morbidity and Mortality after Radical Cystectomy in Carcinoma Urinary Bladder; A Single Centre Experience - Ahmad, Anwaar; Muhammad Rafiq Zafar; Ali, Adnan; Riaz, Omer; Arif, Abdul Jabbar; Sufyan, Abu (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the 30-day morbidity and mortality after radical cystectomy in carcinoma urinary bladder using a validated system. Study Design: Retrospective longitudinal study. Place and Duration of study: Armed Forces Institute of Urology, Rawalpindi Pakistan, from Jun 2016 to Jul 2021. Methodology: After Institutional Ethical Review Board approval, data of all patients of carcinoma urinary bladder who underwent radical cystectomy during five years at Armed Forces Institute of Urology, was collected. Data was retrieved retrospectively from the hospital operative database, indoor patient records and by contacting the patients on their given telephone numbers. Results: In the study population (n=39), a male preponderance was found (36,92.3%). Mean age was 56.7±8.96 years (range 32-72). 26(66.7%) patients were smokers and 16(41%) received neoadjuvant chemotherapy. 9(23.7%) patients had Clavien-DindoGrade-I complications, 6(15.38%) had Grade-II, 2(5.12%) had Grade- IIIA, 2(5.12%) Grade IIIB, 1(2.56%) Grade-IVA, 1(2.56%)had Grade IVB, 2(5.12%) had Grade V complications. The total complications were 23(58.97%), and 16(41.03%) patients had nopost-operative complications. 21(53.85%) patients had less than 14 days post-op operative hospital stay, and 18(46.15%) hadmore than 14 days post-op operative hospital stay. Conclusion: Radical cystectomy is still associated with high early post-op mortality and morbidity. Careful patient selection and thorough counselling before the procedure are very important.